Cognitive Impairment and Carbamazepine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The effects on cognition of carbamazepine, phenytoin and sodium valproate were compared in 64 new cases of childhood epilepsy treated at the Leeds General Infirmary, England.